Multiple Coincident Eruptive Seismic Tremor Sources During the 2014-2015 Eruption at Holuhraun, Iceland - Eibl, Eva P. S.; Bean, Christopher J.; Jónsdóttir, Ingibjörg; Höskuldsson, Armann; Thordarson, Thorvaldur; Coppola, Diego; Witt, Tanja; Walter, Thomas R. (Journal of Geophysical Research: Solid Earth, 2017)
We analyze eruptive tremor during one of the largest effusive eruptions in historical times in Iceland (2014/2015 Holuhraun eruption). Seismic array recordings are compared with effusion rates deduced from Moderate Resolution Imaging Spectroradiometer recordings and ground video monitoring data and lead to the identification of three coexisting eruptive tremor sources. This contrasts other tremor studies that generally link eruptive tremor to only one source usually associated with the vent. The three sources are (i) a source that is stable in back azimuth and shows bursts with ramp-like decrease in amplitude at the beginning of the eruption: we link it to a process below the open vents where the bursts correlate with the opening of new vents and temporary increases in the lava fountaining height; (ii) a source moving by a few degrees per month while the tremor amplitude suddenly increases and decreases: back azimuth and slowness correlate with the growing margins of the lava flow field, whilst new contact with a river led to fast increases of the tremor amplitude; and (iii) a source moving by up to 25∘ southward in 4 days that cannot be related to any observed surface activity and might be linked to intrusions. We therefore suggest that eruptive tremor amplitudes/energies are used with caution when estimating eruptive volumes, effusion rates, or the eruption explosivity as multiple sources can coexist during the eruption phase. Our results suggest that arrays can monitor both the growth of a lava flow field and the activity in the vents. European Commission - Seventh Framework Programme (FP7)